Phase Equilibria in the Al–Co–Cr–Fe–Ni High Entropy Alloy System: Thermodynamic Description and Experimental Study - Stryzhyboroda, Oleg; Witusiewicz, Victor T.; Gein, Sergej; Röhrens, Daniel; Hecht, Ulrike (Frontiers in Materials, 2020)
In this paper we present and discuss phase equilibria in the quaternary Al-Cr-Fe-Ni and the quinary Al-Co-Cr-Fe-Ni alloy systems based on experimental data from DTA/DSC, SEM/EDS and SEM/EBSD on as-cast and isothermally annealed samples. These data as well as literature data were used for developing a new Al-Co-Cr-Fe-Ni thermodynamic description by the CALPHAD approach. Considerable efforts in this direction have been made already and commercial databases for high entropy alloys are available, e.g. TCHEA4 and PanHEA. We focus on comparing our new thermodynamic database with computations using TCHEA4 for two section planes i.e. quaternary AlxCoCrFeNi and quinary AlxCrFe2Ni2, where x is the stochiometric coefficient. According to our new thermodynamic description a single-phase field BCC-B2 is stable over a wider temperature range in both section planes, giving rise to dual-phase microstructures along solid state phase transformation pathways. In the section plane AlxCoCrFeNi the two-phase field BCC-B2+σ predicted by the new database is stable between 600°C and 800°C, while in TCHEA4 this phase field extends to nearly 1000°C. Furthermore, our new database showed that the solidification interval with primary BCC-B2 phase in quinary as well as quaternary section planes is narrow, being in a good agreement with presented micro-segregation measurements. Additionally, computed phase fields and phase-field boundaries in the quinary section plane correspond well to the experimental results reported in the literature.